2019
DOI: 10.1007/s11605-018-3921-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical Inspection of the Gallbladder in Relation to Final Pathology

Abstract: The present prospective study shows that the surgeon should be able to select those gallbladders needing a microscopic gallbladder examination. Potentially, about 80% of this kind of routine histology can be reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional 18 studies were identified during manual cross‐referencing, resulting in a total of 73 articles, including 232 155 patients, that were eligible for data analysis. These studies were then divided into those performed in countries with a low incidence (39) 6,18–55 and countries with a high incidence (34) 7,56–88 of GBC. Characteristics of all included studies are presented in Table S1 (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 23,28,52 (5633 patients) from countries with a low incidence of GBC in which the surgeon systematically inspected the gallbladder mucosa were included in the subgroup analysis. This resulted in an incidence of truly incidental GBC of 0·04 (95 per cent c.i.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of gallbladder cancer (GBC), an extended cholecystectomy is only indicated for stage T1b and above 10. Unfortunately, prospective studies regarding macroscopic assessment of appendiceal specimens by the surgeon are lacking, and the few prospective studies investigating the ability of surgeons to identify macroscopic abnormalities in gallbladder specimens are limited by the small numbers of patients 11–13…”
Section: Introductionmentioning
confidence: 99%